A fortuitous ant-fern association in the Amazon lowlands of Peru - León, Blanca (2010)
Myrmecophyly is best documented among tropical epiphytes, and myrmecotrophy occurs especially among domatia-forming plants. We report the case of Polytaenium cajenense with "external" domatia and its use by the same symbiont ant as its host Cordia nodosa. This case is interpreted as the result of stochastic events and their relations to pre-existing adaptations of all species involved.